Drug regimen compliance issues in clinical trials and patient management - Metry, Jean-Michel; Meyer, Urs A. (John Wiley & Sons, 1999)
This is a study of patients' dosing habits and their negligence with regard to taking the medication in the manner specified. The concept of drug regime compliance brings with it many theories relating to the benefits (or otherwise) of improving patient compliance.